Menulis Ulang Keadilan: Bagaimana Doktrin Suppression of Evidence dalam Preseden Amerika Serikat Menata Kembali Prosedur Peradilan Pidana - Kadir, Zul Khaidir (Universitas Sains dan Teknologi Komputer, 2024)
Suppression of evidence is one mechanism to ensure that law enforcement actions that violate constitutional rights will not produce evidence that can be used in court. Unfortunately, this doctrine is valued for its ability to ensure that the law enforcement process is carried out in accordance with applicable legal rules, as well as maintaining a balance between state power and individual freedom. On the other hand, the application of this doctrine can acquit perpetrators of crimes suspected of committing substantial crimes only because of minor procedural errors made by law enforcement. This study uses a data collection method collected using library research, then analyzed using qualitative methods and presented descriptively. The results of the study indicate that the doctrine of suppression of evidence has proven to be an important mechanism in maintaining a balance between individual constitutional rights and the state's need to enforce the law effectively. In the United States, the exclusionary rule and its various exceptions serve as a barrier to abuse of power by the state and law enforcement, especially in the context of unauthorized searches and seizures. Although it raises concerns that the criminal justice system is becoming less effective, this doctrine remains important in protecting individual constitutional rights in the United States.